â€œPengaruh Jarak Tanam Terhadap Pertumbuhan Dan Produksi Padi Sawah Menggunakan Metode SRI (System Of Rice Intensification)â€ - Helen Maitulung; Jeanne Paulus; Stanley Walingkas; Tommy Ogie (COCOS, 2015)
ABSTRACT Research â€œEffect Of Plant Spacing On Growth and Production Of Rice Using SRI method ( System Of Rice Intensification)â€ held in the village Taratara one for four months, from July 2014 until November 2014, to determine the effect of plant spacing on growth on production of paddy rice varieties with Cigeulis using the SRI method.Â  This study uses a randomized block design with treatment plant spacing J1 ( 25 cm x 25 cm ), J2 (30 cm x 30 cm ), J3 ( 35 cm x 35 cm ), J4 ( 40 cm x 40 cm ) and five replication. Treatment plant spacing significantly affected productive tillers, dry harvest grain plot, dry milled grain plot, and not significantly different effect plant height, weight of 1000 grains, the percentage of grain per panicle pithy.Â  The number ofÂ  productive tillers, dry grain harvested per plot and dry milledÂ Â  per plot the highest in the treatment of 30 cm x 30 cm, 35 cm x 35 cm and 40 cm x 40 c, with the value of each number of tillers per clump 21,08 ; 21,78 and 22,20 of productive tillers.Â  the percentage of grain per panicle pithy 139,60 ; 148,20 dan 156,76 grain.Â  Dry harvested grain per plot 14,34 ; 14,52 and 14,78 kg. Dry milled grain per plot 9,46 ; 9,73 and 10,04 kg. Keyword: Plant Spacing, peddy,SRI Method (System Of Rice Intensification)